2016
DOI: 10.1177/0271678x16678240
|View full text |Cite
|
Sign up to set email alerts
|

Cerebral glycogen in humans following acute and recurrent hypoglycemia: Implications on a role in hypoglycemia unawareness

Abstract: Supercompensated brain glycogen levels may contribute to the development of hypoglycemia-associated autonomic failure (HAAF) following recurrent hypoglycemia (RH) by providing energy for the brain during subsequent periods of hypoglycemia. To assess the role of glycogen supercompensation in the generation of HAAF, we estimated the level of brain glycogen following RH and acute hypoglycemia (AH). After undergoing 3 hyperinsulinemic, euglycemic and 3 hyperinsulinemic, hypoglycemic clamps (RH) on separate occasio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
12
1

Year Published

2017
2017
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(15 citation statements)
references
References 41 publications
2
12
1
Order By: Relevance
“…Oz et al [18] used 13 C magnetic resonance spectroscopy in conjunction with [1-13 C]glucose administration measure brain glycogen content and metabolism in patients with type 1 diabetes and hypoglycemia unawareness, as well as healthy volunteers. This study also did not support the hypothesis that post-hypoglycemia glycogen supercompensation is the driver for hypoglycaemia unawareness [18], although a single hypoglycaemia episode was shown to elicit glycogen supercompensation in healthy subjects [12,16]. Nevertheless, increased brain glucose storage could be favoured by increased glucose uptake after hypoglycaemia.…”
Section: Discussioncontrasting
confidence: 68%
See 1 more Smart Citation
“…Oz et al [18] used 13 C magnetic resonance spectroscopy in conjunction with [1-13 C]glucose administration measure brain glycogen content and metabolism in patients with type 1 diabetes and hypoglycemia unawareness, as well as healthy volunteers. This study also did not support the hypothesis that post-hypoglycemia glycogen supercompensation is the driver for hypoglycaemia unawareness [18], although a single hypoglycaemia episode was shown to elicit glycogen supercompensation in healthy subjects [12,16]. Nevertheless, increased brain glucose storage could be favoured by increased glucose uptake after hypoglycaemia.…”
Section: Discussioncontrasting
confidence: 68%
“…Evidence supporting this post-hypoglycemia supercompensation has been reported in the human [12,16], rat [9,14], mouse [10] and rainbow trout [15]. However, the re-establishment of glycogen content in the brain after hypoglycaemia has been involved in controversy: (1) not all studies confirmed glycogen supercompensation after acute hypoglycaemia [11], (2) there have been reports suggesting that repeated hypoglycaemia does not result in increased glycogen levels [11,16,17], and (3) patients with type 1 diabetes and hypoglycaemia unawareness display brain glycogen levels similar to those in healthy subjects [18].…”
Section: Introductionsupporting
confidence: 55%
“…Various mechanisms, including changes in glucose uptake or metabolism by the brain, the use of alternate fuels, and changes in hypothalamic neurotransmitter release have been proposed. Excessive compensation of brain glycogen levels during recurrent hypoglycemia could contribute to the development of hypoglycemia-associated autonomic failure in humans (15). Inhibition of the counterregulatory response by suppressed adrenal activity has been observed in animal models (16).…”
Section: Discussionmentioning
confidence: 99%
“…However, many of these studies were conducted in people or rodents without type 1 diabetes. More recent work suggests no increase in cerebral glucose metabolism during hypoglycaemia in people with type 1 diabetes and IAH [30] and no increase in brain glycogen stores [31]. Moreover, compared with control animals, detailed tracer studies in rodents indicate that, after recurrent hypoglycaemia, neuronal glucose metabolism is actually decreased during subsequent hypoglycaemia [32].…”
Section: Why Do People With Diabetes Develop Iah?mentioning
confidence: 99%